0.3x+0.1=0.5x-0.9

Simple and best practice solution for 0.3x+0.1=0.5x-0.9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.3x+0.1=0.5x-0.9 equation:



0.3x+0.1=0.5x-0.9
We move all terms to the left:
0.3x+0.1-(0.5x-0.9)=0
We get rid of parentheses
0.3x-0.5x+0.9+0.1=0
We add all the numbers together, and all the variables
-0.2x+1=0
We move all terms containing x to the left, all other terms to the right
-0.2x=-1
x=-1/-0.2
x=+5

See similar equations:

| 10(x+1)=-2(2x+9) | | a^2+a^2=20 | | 4(x-1)-3=6x-2(-2+x) | | 0.66/4=x/6 | | -4(2x+3)=-36 | | 21.01-12+5x3.5= | | 1.66/x=1/10 | | 1-3x=15+4x | | 5x+5=(x+7) | | x18-18x-1=73 | | -22=22+f | | 8-5x+37=36 | | 4-x=3x-4x | | 7-5x+37=36 | | 10/x=6/1.66 | | X=x/5-11 | | 1/6(12x-18=2(x-3/2) | | 6/1.66=10/x | | y/12+2=-18 | | 7×3x+37=36 | | 26-7x=-23 | | X^2(2x-3)-1=0 | | 4(2x+3)=13(x-1) | | 1.66*6=10*x | | 11+3v-4v=6v-3 | | 6-3x+37=36 | | 3x/10=2x/3-11 | | 27-y=9 | | -1=4(x-4)-(x-6) | | 5-2x+37=36 | | 4-4x+37=36 | | 1.66*6=x*10 |

Equations solver categories